2018
DOI: 10.9734/jamps/2018/43626
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Potential of Clonally Propagated Prunella vulgaris L. under in vitro Conditions

Abstract: Aims:The study aims to determine the antibacterial efficacy of Prunella vulgaris plant produced by micropropagation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…In addition, the 2020 edition of Chinese Pharmacopoeia stipulated that rosmarinic acid was used as the content determination index of its quality control. Modern pharmacological studies have shown that it has extensive pharmacological activities, and has certain pharmacological effects on anti-tumor, antibacterial and antiviral, anti-inflammatory and immune regulation, antihypertensive, hypoglycemic, hypolipidemic, antioxidant and free radical scavenging, liver protection and so on ( Ryu et al, 1992 ; Fang et al, 2005a ; Sárosi and Bernath, 2008 ; Kim, 2012 ; Zhang et al, 2014 ; Huang et al, 2015 ; Raafat et al, 2016 ; Çetin and Kalyoncu, 2018 ; Ahmad et al, 2020 ; Zhang et al, 2020 ). More than any of these, its excellent quality and remarkable curative effect have also been highlighted in clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 2020 edition of Chinese Pharmacopoeia stipulated that rosmarinic acid was used as the content determination index of its quality control. Modern pharmacological studies have shown that it has extensive pharmacological activities, and has certain pharmacological effects on anti-tumor, antibacterial and antiviral, anti-inflammatory and immune regulation, antihypertensive, hypoglycemic, hypolipidemic, antioxidant and free radical scavenging, liver protection and so on ( Ryu et al, 1992 ; Fang et al, 2005a ; Sárosi and Bernath, 2008 ; Kim, 2012 ; Zhang et al, 2014 ; Huang et al, 2015 ; Raafat et al, 2016 ; Çetin and Kalyoncu, 2018 ; Ahmad et al, 2020 ; Zhang et al, 2020 ). More than any of these, its excellent quality and remarkable curative effect have also been highlighted in clinical application.…”
Section: Introductionmentioning
confidence: 99%